2012
DOI: 10.1530/joe-11-0488
|View full text |Cite
|
Sign up to set email alerts
|

β (CCL2) and α (CXCL10) chemokine modulations by cytokines and peroxisome proliferator-activated receptor-α agonists in Graves' ophthalmopathy

Abstract: No data are present in the literature about the effect of cytokines on the prototype b chemokine (C-C motif) ligand 2 (CCL2) or of peroxisome proliferator-activated receptor a (PPARa (PPARA)) activation on CCL2 and CXCL10 chemokines secretion in fibroblasts or preadipocytes in Graves' ophthalmopathy (GO). We have tested the effect of interferon g (IFNg (IFNG)) and tumor necrosis factor a (TNFa) on CCL2, and for comparison on the prototype a chemokine (C-X-C motif) ligand 10 (CXCL10), and the possible modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…44,45 Recent research has shown that peroxisome proliferator-activated receptor-α (PPARα) agonists may exert immunomodulatory effects in GO by inhibiting various chemokines secreted by GO fibroblasts and preadipocytes. 46,47 Perhaps addressing this pathogenic mechanism will help reduce the chance of disease recurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Recent research has shown that peroxisome proliferator-activated receptor-α (PPARα) agonists may exert immunomodulatory effects in GO by inhibiting various chemokines secreted by GO fibroblasts and preadipocytes. 46,47 Perhaps addressing this pathogenic mechanism will help reduce the chance of disease recurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, lower glucocorticoid doses would imply a smaller PPAR-g-mediated inflammatory response. However, there has been evidence suggesting that the anti-inflammatory potential of this receptor activation would not be as significant as that of other receptors from the same family, such as PPAR-α (4) . Therefore, considering the preponderant action of PPAR-g on adipogenesis, when opting for glucocorticoids in the treatment of GO, we could speculate that the ideal would be not using low doses, which would stimulate expression of the receptor, increasing the adipocyte differentiation and contributing to progression of the exophthalmos.…”
Section: Graves Ophthalmopathy: Low-dose Glucocorticoid Increases Permentioning
confidence: 98%
“…Another point of concern has been the inflammatory response, a result of the release by monocytes and macrophages of cytokines and other mediators, which can contribute significantly to the progression of the condition and implies that corticotherapy should be the main therapeutic approach (3) . Unlike what happens in the adipocyte pathway, PPAR-g activation has been associated with inhibition of the inflammatory process induced by certain cytokines (4) , which raises doubts about the final balance of receptor stimulation regarding the evolution of GO. Furthermore, the possible relation of PPAR-g with the treatment of an ocular condition with glucocorticoids remain to be clarified.…”
Section: Graves Ophthalmopathy: Low-dose Glucocorticoid Increases Permentioning
confidence: 99%
See 1 more Smart Citation
“…Also orbital fibroblasts and preadipocytes from patients with Graves' ophthalmopathy are able to secrete CXCL10, CXCL9, and CXCL11 chemokines, under the influence of IFN-γ, and the combination of IFN-γ and tumor necrosis factor (TNF)-α [7][8][9].…”
Section: Role Of Cxcl9 Cxcl10 and Cxcl11 In Thyroid Associated Autoimentioning
confidence: 99%